Pyoderma gangrenosum following anti-TNF therapy in chronic recurrent multifocal osteomyelitis: drug reaction or cutaneous manifestation of the disease? A critical review on the topic with an emblematic case report - Romagnuolo, Maurizio; Moltrasio, Chiara; Iannone, Claudia; Gattinara, Maurizio; Cambiaghi, Stefano; Marzano, Angelo Valerio (Frontiers in Medicine, 2023)
Chronic recurrent multifocal osteomyelitis (CRMO) is a rare autoinflammatory disease, clinically characterized by chronic and recurrent episodes of osteoarticular inflammation, that generally presents in children and adolescents. From a dermatological point-of-view, CMRO can be associated with skin rashes mainly including psoriasis, palmoplantar pustulosis and acne. Pyoderma gangrenosum (PG) is a rare immune-mediated inflammatory skin disease classified within the spectrum of neutrophilic dermatoses that, in some cases, has been reported as cutaneous manifestation in CMRO patients. This paper presents a 16-year female patient diagnosed with CMRO, who presented PG lesions located on the lower leg, that arose after the administration of the tumour necrosis factor (TNF)-α inhibitor adalimumab. Cases of PG have been reported in patients being treated with certain medications, including TNF-α antagonists, leading to classified them in a setting aptly termed “drug-induced PG.” In this paper, we discuss the co-occurrence of PG and CRMO, in the light of recent evidence on the pathogenesis of both diseases and giving ample space to a literature review on drug induced PG. In our case, it is plausible that PG could be considered a cutaneous manifestation of CRMO, although the mechanisms underlying this intriguingly relationship remain to be fully unraveled.